PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN MELALUI KEPUTUSAN PEMBELIAN SEBAGAI VARIABEL INTERVENING (Studi Kasus Pada Produk Ayam Broiler Di PT. Mitra Peternakan Unggas Unit Pandeglang) - Yeni Firmawati (LPPM UNIVERSITAS INSAN PEMBANGUNAN INDONESIA, 2022)
ABSTRACT Broiler Chicken Farms have very good prospects for development, both on a large and small scale. Broilers are the only poultry that have an important role because they produce meat that provides the availability of animal protein, the manure can be used as organic fertilizer and the feathers can be used as industrial materials. One of the companies engaged in the field, especially Broiler Chicken is PT.Mitra Poultry Farm. PT. Mitra Poultry Farm, which is located in the Cigadung Indah Complex Block C/21 RT/RW 03/05, Cigadung Village, Karang Tanjung District, Pandeglang Regency, Banten. To be able to compete in this broiler farming business, the company must improve product quality and good service quality in order to create customer purchasing decisions for broiler chickens optimally so that it will have an impact on customer satisfaction of broiler chicken products at PT Mitra Peternakan Poultry Unit Pandeglang. Based on this, this research raises the title